Katharine Worth (1922-2015) - Cave, Richard Allen (Open Book Publishers, 2016)
It was fitting that at the funeral of Katharine Worth, who died on 28th January 2015 at the age of ninety-two, her daughter quietly read The Wild Swans at Coole. It had been the poem that Katharine had chosen to read and discuss with a poetry group in the home where she spent the final months of her life. The echoes and resonances at that moment were many and various: recall of the years Katharine taught at the Yeats International Summer School at Sligo; realisation of the extent to which Yeats...